Iron‐mediated activators generated by electron transfer for atom‐transfer radical polymerization of methyl methacrylate using ionic liquid as ligand and Fe(0) wire as reducing agent. Issue 12 (24th August 2015) - Bai, Liangjiu; Huang, Suqi; Wang, Wenxiang; Xu, Hui; Chen, Hou; Niu, Yuzhong; Wang, Minghua
Abstract 1‐Butyl‐3‐methylimidazolium hexafluorophosphate (BMIMPF6) as a typical ionic liquid (IL) effectively acted as ligand for the control of iron‐mediated activators generated by electron transfer for atom‐transfer radical polymerization of methyl methacrylate (MMA) in the presence of a limited amount of oxygen, using FeCl3.6H2O as the catalyst and Fe(0) wire as the reducing agent. The polymers obtained with BMIMPF6 had controlled molecular weights and low Mw/Mn values (<1.40). Moreover, a well‐defined final product PMMA without additional processing was easily obtained and the reducing agent (iron wire) could be recycled and reused effectively just by washing three times with solvents.